Efektivitas Kelopok Tani sebagai Media Komunikasi Pembangunan Pertanian di Kecamatan Cangkringan Kabupaten Sleman - Eva Trisanti (Jurnal Dinamika Sosial Ekonomi, 2004)
Institutional aspect is importance in agriculture development, it become an activator for increasing the farmer's role and responsibility. Farmer group as one of the institutions in agriculture development has a role in learning actuivities,  production unit, and cooperation medium. In such group, knowledge and skill of funner can be developed and mutual cooperations is mantained. The research aims to study the effectiveness of farmer group as medium for communication in agriculture development and to identify the factors influencing the effectiveness. The results of this research showed that the effectiveness of farmer group in agriculture development can be categorized as high (61.67 percent) Cangkringan subdistrict, Sleman district. It was indicated by higher member activity in knowledge and skill development (5,33 percents) and in dessimination of agricultural pormation (53,37 percents). Chi-square analysis indicated that the cohesiveness, education motivation, and perception of members and that group leadership have influenced obviously to farmer group effectiveness in the communication in agriculture development Keywords: effectiveness, former group, communication medium, agriculture development